Stabilization of stochastic complex-valued coupled delayed systems with Markovian switching via periodically intermittent control. (August 2018) - Wang, Pengfei; Hong, Yu; Su, Huan
Abstract: This paper focuses on exponential stabilization of stochastic complex-valued coupled delayed systems with Markovian switching (SCCDM) via periodically intermittent control. The features of complex-valued systems, time-varying delays, stochastic disturbances and Markovian switching are taken into account. The mathematical model of this kind of complex-valued coupled systems is studied for the first time. To study the stabilization problem of SCCDM, two new differential inequalities on delayed Markovian jump systems are established. Then by utilizing Lyapunov method combined with Kirchhoff's Matrix Tree Theorem, sufficient criteria promising the stability of SCCDM via periodically intermittent control are derived, which have a close relationship with control period, control rate, control gain and the topological structure of the considered coupled network. Then we employ the theoretical results to study the stabilization problem of stochastic complex-valued coupled oscillators with Markovian switching via periodically intermittent control. Finally, numerical examples are provided to demonstrate the effectiveness and feasibility of the proposed results.